The study oil road traffic injuries (RTL) in Kudat, Sabah State, Malaysia - Tin, Tin Myint; Khin, Daw Saw Naing (Universiti Malaysia Sabah, 2008)
With rapid urbanization of rural areas in Sabah, road traffic injuries are gaining higher ranks among the top priority hospital admissions. According to 2006 data, road traffic injuries and related cases ranked third and accounted for 7.75% of all hospital admissions in 10 Government Hospitals. The problem is considered to be in a rising trend as the number of motor vehicles used by the rural population is escalating. A retrospective case reviews of all cases of road traffic injuries, who sought treatment during January to December 2008, was conducted at the district hospitals of Kudat and Kota Marudu. Review of medical records was made and demographic data like age, sex and the relevant data such as type of road users, time of accident, type of vehicle , sites and type of wound as well as type of injury sustained were retrospectively collected. A total of 203 road traffic injuries were covered. Out of which, 68% were male. The highest percentage (30%) was found in the age group of 21-30 years. Passengers formed the major group of people affected by road traffic injuries. Nearly one fourth was noted to be suffering from severe bone injuries while more than one third of cases required referral to Queen Elizebeth hospital, Kota Kinabalu. Common sites of injury were head, face and limbs. According to 2004 statistics, the population in Kudat was 76046 within 1287.2sqkm while Kota Marudu has 70051 population within the area of 19170 sq km. It was estimated that 14 road traffic injuries cases to every 10,000 population occurred in year 2008, in these areas. Associated mortality at the time of accident was more than 4%. The study revealed the magnitude of road traffic injuries in terms of morbidity and mortality. The extent of injuries and the nature of bony involvements indicated the burden of road traffic injuries on medical and health care system. Thus the findings of this study would provide baseline data for the hospital planners and administrators to plan ahead for emergency measures as well as appropriate care of road traffic injuries in the area.